Kesan Penggunaan Garam Ammonium Kuaterner Di Dalam Getah Terisi Hitam Karbon Dan Silika - Ahmad, Zulkifli (2001)

(untitled)
Kehadiran suatu aditif yang boleh mempamerkan kepelbagaian fungsi akan meningkatkan keefisienan percampuran getah serta mengurangkan kos pengeluaran. Dalam kajian ini satu aditif berbentuk garam ammonIum kuaterner iaitu cetiltrimetilammonium maleate CTMAM) telah disintesiskan untuk dikaji kesannya terhadap ciri pemprosesan dan sifat mekanik vulkanisat getab asli dan sintetik polikloropena. Kesan pengisi hitam karbon dan silika dengan kehadiran aditif ini juga dikaji termasuk tahap taburan pengisi tersebut ke dalam matrik getah. The presence of a multi-functional additive in the rubber formulation will enhance processing efficiency and cost reduction. Cetyltrimethylammonium maleate, a quaternary ammonium salt is synthesised and used as an additive to study its effect on processing and mechanical properties of natural rubber and polychloroprene. The study shows a marked decreased in scorch time with an increase in rate ofvu1canisation having an optimum effect at 1 - 2 phr. The calculated activation energy increased correspondingly with the increase in the additive concentration. An inhibitor, PVI, is found to reduce the scorchiness of the vulcanisate without imparting loss in processing and mechanical properties. The latter are improved with the addition of the additive again reaching optimum at concentration of 1 - 2 phr.